Modeling and Simulation of Hybrid Vehicle Control System by Using MATLAB Simulink - Nguyen, Văn Long Giang; Le, Văn Miền (Journal of Technical Education Science, 2023)
Nowadays, automotive manufacturers are increasingly leading the development of hybrid vehicles due to growing energy consumption and increased emissions. The power-split hybrids, due to the simultaneous use of speed and torque couplings, have integrated the advantages of series and parallel hybrid systems and minimized their disadvantages [1]. However, optimization of its operation mode depends on many components, such as an internal combustion engine (ICE), traction motor (MG2), motors and generators (MG1), a battery, and a power-split device [2]. Therefore, the control strategy development for power-split hybrid electric vehicles (HEV) always needs to be improved and developed. This study is no exception, focusing on control strategies of power flow in a power-split HEV system. The control system model had been built with the MATLAB/Simulink package, and the simulation results showed optimal operation of each component in the control system. Fuel consumption of ICE decreased by 54,79% and 53,09% in two typical driving cycle tests (NEDC and FTP-75), and emissions of the three main components in the exhaust gas CO, HC, decreased by 0,39%, 0,26%, and 0,93%, respectively, according to the NEDC, and by 4,4%, 4,9%, and 3,7%, according to the FTP-75 driving cycle test.